Studies on Blackening of Canned Prawns 1.Influence of Copper and Iron on Product Blackening - NANDAKUMRAN, M.; CHAUDHUIU, D R.; PILLAI, V. K. (Fishery Technology, 2025)
A linear relationship was observed between the coppercontent and intensity of blackening in commercially canned prawnmeat. Average copper and iron contents of unblackened cannedprawn meat were 9.6 and 32.5 ppm on dry weight basis respectively.ln the blackened product copper content ranged from 15.8 to 63.9ppm and iron content between 43.7 and 71.45 ppm depending on theintensity of blackening. But incorporation of copper in the aboveraege to experimental cans produced blackening while iron upto 250ppm did not impart any blackening under standard conditions ofcanning.